1994
DOI: 10.1093/ajcn/60.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effectiveness of iron-folate supplementation and anthelminthic therapy against anemia in pregnancy— a study in the plantation sector of Sri Lanka

Abstract: Intervention measures against anemia available to plantation workers during pregnancy include fortified food supplements (thriposha) and iron-folate supplements containing 60 mg elemental Fe. The effectiveness of these intervention measures was studied in 195 subjects whose iron and nutritional status were assessed at < 24 and > 32 wk of gestation. Taking thriposha conferred no significant benefit on maternal nutritional status, probably because sufficient amounts were not consumed. An increase in the duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 11 publications
1
68
0
1
Order By: Relevance
“…He observed that in the iron-supplemented group there was an initial decline in the Hb concentration until about 28 progressive weeks of gestation, but increasing until term. Atukorala et al (1994) also observed an identical trend among plantation workers of Sri Lanka only among those who took one iron and folic acid tablet daily. Their Hb at 32 ± 40 weeks was signi®-cantly (P`0.05) higher than at 14 ± 24 weeks of gestation.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…He observed that in the iron-supplemented group there was an initial decline in the Hb concentration until about 28 progressive weeks of gestation, but increasing until term. Atukorala et al (1994) also observed an identical trend among plantation workers of Sri Lanka only among those who took one iron and folic acid tablet daily. Their Hb at 32 ± 40 weeks was signi®-cantly (P`0.05) higher than at 14 ± 24 weeks of gestation.…”
Section: Discussionmentioning
confidence: 51%
“…Community-based studies to understand the impact made on the prevalence and mean values of haemoglobin and serum ferritin (SF) concentration in each of the three trimesters are scanty. The available community-based trials (Atukorala et al, 1994) also focused and followed the same groups of women to see the effect of the supplementation. The present communitybased study attempts to understand the changes that could occur in the haematological status among the pregnant women in a rural community in three trimesters with the intervention of iron supplementation, helminthic control and other effective strategies through information, education and communication (IEC).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc levels in maternal milk were determined in a similar manner (C.V. 4.9%). Atukorala et al (1994) indicate that the normal limit for serum zinc levels in pregnant women is 8 mmolaL. Other ®gures quoted are 10.7 mmolaL according to Jameson (1975), and 12.2 mmolaL according to Pfeffer et al (1996).…”
Section: Biochemical Studymentioning
confidence: 96%
“…It has the highest prevalence in the US among women and young children. Women ages [16][17][18][19] have an iron deficiency incidence as high as 19%. Iron deficiency increases in minority populations and is as high as 22% in Hispanic women.…”
Section: Introductionmentioning
confidence: 99%
“…In India 20% of maternal deaths are due to anemia. In the Ivory Coast [17], Sri Lanka, and Sierra Leone, treatment for hookworm improved hemoglobin levels significantly [18,19]. A study involving 3595 children attributed 35% of cases of iron deficiency anemia and 73% of cases of severe iron deficiency anemia to hookworm infection [20].…”
Section: Introductionmentioning
confidence: 99%